Hubungan MotivasiBerpuasa Sunah Terhadap Pengendalian Emosi Pada Santri MTS di Pondok PesantrenNurul Qomar - Halima, Halima Halima; ., Halima; Noupal, Muhammad; Pri Handiki, Yulian Rama (Jurnal Spiritual Healing, 2024)
Fasting Motivational Therapy on anger emotion control among middle school students at Nurul Qomar Islamic Boarding School in Palembang. The study also aims to measure the benefits of this therapy in enhancing emotional control among students. Employing quantitative methods, the correlation technique was used to investigate the relationship between the motivation to perform sunnah fasting and the emotional regulation of students. The research population included approximately 85 students at the middle school level of Nurul Qomar Islamic Boarding School. Simple regression analysis was utilized using SPSS 25 for Windows. The results revealed a positive correlation between the practice of sunnah fasting and emotional control among students, as indicated by a correlation coefficient of 0.708 and a significance level (p-value) less than 0.01. This suggests that motivational therapy for Monday-Thursday sunnah fasting significantly impacts students' emotional regulation. Furthermore, the findings highlight that a higher commitment to sunnah fasting correlates with better mental and spiritual health, enabling students to regulate their emotions effectively.